2022
DOI: 10.3390/antiox11091685
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nrf2 in Pulmonary Fibrosis: Molecular Mechanisms and Treatment Approaches

Abstract: Pulmonary fibrosis is a chronic, progressive, incurable interstitial lung disease with high mortality after diagnosis and remains a global public health problem. Despite advances and breakthroughs in understanding the pathogenesis of pulmonary fibrosis, there are still no effective methods for the prevention and treatment of pulmonary fibrosis. The existing treatment options are imperfect, expensive, and have considerable limitations in effectiveness and safety. Hence, there is an urgent need to find novel the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 181 publications
0
7
0
Order By: Relevance
“…In the late stage of RILI, PF is a consequence of delayed radiation effects and is often considered an irreversible hazard [ 4 , 88 ]. Recent clinical studies have shown that Nrf-2 is associated with radiation-induced PF, and Nrf-2 activators have demonstrated anti-fibrotic effects [ 89 ]; this is mainly because Nrf-2 deficiency inhibits the mobilization of ΔNp63 stem/progenitor cells while amplifying the tendency of alveolar type 2 cells to convert into myofibroblasts under radiation induction [ 64 ]. In the injured lung, Δp63+/Krt5+ stem cells are significantly mobilized and proliferate.…”
Section: The Potential Role and Mechanisms Of Nrf-2 In Radiation Indu...mentioning
confidence: 99%
“…In the late stage of RILI, PF is a consequence of delayed radiation effects and is often considered an irreversible hazard [ 4 , 88 ]. Recent clinical studies have shown that Nrf-2 is associated with radiation-induced PF, and Nrf-2 activators have demonstrated anti-fibrotic effects [ 89 ]; this is mainly because Nrf-2 deficiency inhibits the mobilization of ΔNp63 stem/progenitor cells while amplifying the tendency of alveolar type 2 cells to convert into myofibroblasts under radiation induction [ 64 ]. In the injured lung, Δp63+/Krt5+ stem cells are significantly mobilized and proliferate.…”
Section: The Potential Role and Mechanisms Of Nrf-2 In Radiation Indu...mentioning
confidence: 99%
“…The loss of homeostasis between epithelial and mesenchymal cells and increased resistance of myofibroblasts to apoptosis may then result in the abundant fibroblast activation and accumulation of the extracellular matrix leading to pulmonary fibrosis [ 148 , 150 ]. The above-mentioned changes are associated with a significant oxidative-antioxidant imbalance and GSH deficiency [ 151 , 152 , 153 , 154 ]. Oxidative stress in pulmonary fibrosis is associated mainly with the NF-κB signaling pathway, the Kelch-like ECH-associated protein 1 (Keap1)/Nrf2/ARE pathway, and the NADPH oxidase (NOX)4-Nrf2 signaling cascade [ 155 ].…”
Section: Nac In Chronic Respiratory Diseasesmentioning
confidence: 99%
“…This study will focus on some molecular targets, including Nuclear factor erythroid 2-related factor 2 (Nrf2), a regulatory nuclear factor that influences the activity and cellular response of the antioxidant system 17 , NF-κB, and the inflammasome NLRP3 which are closely related to one another and influence the level of inflammatory and pro-fibrotic cytokines in the microenvironment as well as the apoptosis and senescence of alveolar epithelial cells especially for NF-κB 18 . As for peroxisome proliferator-activated receptor gamma (PPAR-γ), studies have suggested its important role in modulating the inflammatory and fibrotic responses in the lung 19 .…”
Section: Introductionmentioning
confidence: 99%